Nahrungsmittelallergien – Theorie und Praxis - Jappe, Uta (DMW - Deutsche Medizinische Wochenschrift, 2018)
Allergies manifest differently in every patient: Even when the same allergen source is the causing agent, means of sensitization and complexity of symptoms can vary strongly across patients. This often complicates the prevention, diagnostics and therapy of food allergies – or even makes them impossible. This article gives an overview of the underlying immunological principles of food-allergies, as well as of the current therapeutic and diagnostic approaches.
Keywords: Nahrungsmittelallergie; Nahrungsmittelunverträglichkeit; IgE-vermittelte Nahrungsmittelallergie; Anaphylaxie; allergenspezifische Immuntherapie